The Influence of Perceived Usefulness, Perceived Ease of Use, and Artificial Intelligence Integration on E-Commerce Adoption among Food MSMEs in Pasuruan City - Sinta Nuriyaningsih; Antin Rakhmawati (Darul Yasin Al Sys, 2026)
The rapid development of digital technology has encouraged micro, small, and medium enterprises (MSMEs) to adopt e-commerce as a business development strategy. However, such adoption depends not only on technological availability but also on users’ perceptions of its benefits, usability, and emerging technological capabilities. This study examines the effects of perceived usefulness, perceived ease of use, and artificial intelligence (AI) integration on e-commerce adoption among food MSMEs in Pasuruan City. Employing a quantitative explanatory design, the study involved 100 respondents. Data were collected through a structured questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that perceived usefulness has a positive and significant effect on e-commerce adoption, whereas perceived ease of use and AI integration have no significant effects. These results identify perceived business benefits as the primary factor underlying e-commerce adoption among food MSMEs in the study context. The study provides empirical evidence that the perceived value of digital technology may be more consequential to adoption than its perceived usability or AI-enabled capabilities. Accordingly, MSME digitalization strategies should prioritize the delivery and communication of tangible business value, supported by continuous digital training, mentoring, and technological facilitation.